Recent Advances In Biomass-Derived Carbon, Mesoporous Materials, And Transition Metal Nitrides As New Electrode Materials For Supercapacitor: A Short Review - Mohd Abid, Mohd Asyadi 'Azam; Nik Ramli, Nik Suhaini; Tuan Nawi, Tuan Idzuddin; Mohd Nor, Nurul Aini Nadirah (John Wiley and Sons Ltd, 2021)
A suitable electrode or active material is one of the promising ways to boost supercapacitors' efficiency. The right properties of the electrode materials will enhance the performance of the supercapacitors. New electrode materials such as biomass-derived carbon, mesoporous materials, and transition metal nitrides have been studied as potential substitutes for the most common electrode material, activated carbon. This review discusses the recent (5 years) progress of the electrode materials in supercapacitors compiling the literature from 2016 to 2020. The overview of design (structures), recent developments, and challenges of the new electrode materials are presented in this review with considerations on their electrochemical performance in supercapacitors.